PREDICTION OF VIABILITY AND EMERGENCE CAPACITY OF SAFFLOWER SEED LOTS - M. D. Kaya; E. G. Kulan; O. Ileri; S. Avci (Journal of Animal and Plant Sciences, 2019)
Predicting seedling emergence potential of safflower under field conditions is very difficult because of a wide variation of seed size, weight, shape and oil content. This study aimed to determine the most useful seed testing method predicting the field emergence of safflower seed lots. Thirty-four seed lots of 16 safflower genotypes were evaluated for field emergence, germination, seedling growth, accelerated ageing (AA) at 41, 43 and 45 °C for 48, 72, 96, 120 and 144 h, cool germination (18°C) and cold tests (10°C for 7 days), pH and electrical conductivity (EC) values of soak water for 4, 8 and 24 h. The seed lots showed a high variability for germination from 77.0% to 98.5% in laboratory conditions, and the field emergence ranged between 30.5% and 84.5%. The highest correlation with field emergence was detected in the second day germination in cool test (r=0. 586**), followed by the cold (r=0. 556**) and cool germination (r=0. 527**). No significant correlations were determined between the field emergence and seed weight, oil rate, seedling growth parameters, EC, pH and mean germination time. The AA test conducted at 41°C for 48 h significantly related to the field (r=0.492**) and laboratory emergence (r=0.607**); consequently, this combination is advised as the optimum ageing condition. The only one seed testing method does not reflect the emergence potential of safflower seed lots so, the tests should be combined by a linear multiple regression analysis. It was concluded that second day germination in cool test (SDC), laboratory emergence (LE) and cold test (CT) were found the promising methods in order to determine seed vigor of safflower. The best model was discovered as second day germination in cool test, laboratory emergence and cold test with the model of y=-37.8+0.64*SDC+0.17*LE+0.32*CT.
Keywords: Carthamus tinctorius L.; germination; emergence; accelerated ageing; cold test